1998
DOI: 10.1074/jbc.273.24.14813
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Escherichia coli by Insect Hemocytes Requires Both Activation of the Ras/Mitogen-activated Protein Kinase Signal Transduction Pathway for Attachment and β3 Integrin for Internalization

Abstract: Here we report further data of LPS-mediated signal transduction responsible for Escherichia coli phagocytosis. We demonstrate that both adhesion of hemocytes to substrata and LPS stimulation can cause activation of p44 MAPK in Ceratitis capitata hemocytes but with distinct kinetics indicating different functions. In addition, we showed that Drk, a homolog protein to the mammalian GRB2, is implicated in the transmission of LPS signaling, indicating that the Ras/mitogen-activated protein kinase pathway is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 29 publications
4
67
0
Order By: Relevance
“…It has been shown that integrin receptors can be internalized after binding either endogenous ligands (eg, ␣IIb␤3 binding of fibrinogen 32 ) or exogenous ligands (eg, bacteria 33,34 ), and the ␣2␤1 receptor on platelets has also been shown to internalize collagen fragments ex vivo. 21 However, a role for integrin receptor internalization in vivo as a mechanism for dynamically regulating the adhesion of hematopoietic cells that need to migrate extensively has not been previously explored.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that integrin receptors can be internalized after binding either endogenous ligands (eg, ␣IIb␤3 binding of fibrinogen 32 ) or exogenous ligands (eg, bacteria 33,34 ), and the ␣2␤1 receptor on platelets has also been shown to internalize collagen fragments ex vivo. 21 However, a role for integrin receptor internalization in vivo as a mechanism for dynamically regulating the adhesion of hematopoietic cells that need to migrate extensively has not been previously explored.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly there are others, and recent work with LPS is beginning to reveal some of them. Foukas et al (1998) suggested that the Ras/mitogen-activated protein kinase pathway and integrin receptors are required for cellular internalization of LPS by hemocytes from C. capitata. So far, then, eicosanoids, biogenic amines and kinase pathways have been recognized as important elements in mediating cellular defense reactions to bacterial challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The defense system of invertebrates is based on both cellular and humoral immune responses (6). The former includes encapsulation (7)(8)(9), phagocytosis (10), and nodule formation (11). The clotting system of arthropods (12,13), the synthesis of a broad spectrum of potent antimicrobial proteins in many insects (14,15) and crustaceans (16 -18), and the prophenoloxidase activating system (proPO system) (2) belong to the last immune response.…”
mentioning
confidence: 99%